‘Who Shall Ascend into the Hill of the Lord?’: The Religious-Political debate in the Arab World on Ziyarat to Jerusalem - Halevy, Dotan (Jama’a: an Interdisciplinary Journal of Middle East Studies, 2015)
Are non-Palestinian Muslims allowed – according to Sharia law – to visit Al-Aqsa Mosque while the latter is under Israeli control? In recent years there has been a growing engagement with this question amongst muftis, politicians, and public opinion makers throughout the Arab world, following Mahmoud Abbas’ bold call in 2012 to all Arabs and Muslim to perform the commandment of Ziyarat (visitation) to Jerusalem. This article deals with the discussion that has aroused around this issue, maps the various sides that partook in it, and explores its complexity. The article argues that the question of visiting Jerusalem exposes deep conceptual gaps dividing the Arab and Muslim world. First, through the rhetoric use of the categories ‘religion’ and ‘politics’: whilst supporters of Ziyarat to Israeli-controlled Jerusalem mobilise religious arguments in favour of Palestinian political goals, in principal they advocate separation between religion and politics. In contrast, opponents of Ziyarat to Jerusalem see these categories as representing one set of principles – in a similar fashion to political Islam movements – and utilise a hybridised religio-political argument to sustain their stance. Second, through the meaning which is afforded to ‘normalisation’ with the State of Israel: Ziyarat proponents hold a flexible and pragmatic understanding of resistance to normalisation, while Ziyarat opponents see it as an unalterable, nonnegotiable condition